2008
DOI: 10.1074/jbc.m708622200
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Oxidative Stress-induced Hepatic Injury by Intracellular Type II Platelet-activating Factor Acetylhydrolase by Metabolism of Oxidized Phospholipids in Vivo

Abstract: Membrane phospholipids are susceptible to oxidation, which is involved in various pathological processes such as inflammation, atherogenesis, neurodegeneration, and aging. One enzyme that may help to remove oxidized phospholipids from cells is intracellular type II platelet-activating factor acetylhydrolase (PAF-AH (II)), which hydrolyzes oxidatively fragmented fatty acyl chains attached to phospholipids. Overexpression of PAF-AH (II) in cells or tissues was previously shown to suppress oxidative stress-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 73 publications
(38 reference statements)
1
75
0
3
Order By: Relevance
“…The plasma form is secreted by cells of hematopoietic origin and is associated with circulating lipoproteins (Lp-PLA 2 ). The intracellular cytosolic form is expressed mainly in hepatocytes and epithelial cells of kidney and intestine ( 42 ). These phospholipases display high activity with sn -2 oxidized chains of phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma form is secreted by cells of hematopoietic origin and is associated with circulating lipoproteins (Lp-PLA 2 ). The intracellular cytosolic form is expressed mainly in hepatocytes and epithelial cells of kidney and intestine ( 42 ). These phospholipases display high activity with sn -2 oxidized chains of phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that hydrolysis of oxidized phospholipids is a primordial function of PAF-AH. Correspondingly, ablation of the type II PAF-AH sensitizes mice to the toxic effects associated with CCl 4 -induced oxidant stress in the liver (8), showing that this protective role is retained by the mammalian enzyme. These combined observations point to an essential role of PAF-AHs as scavengers of apoptotic, short-chained phospholipids.…”
Section: Apoptosismentioning
confidence: 99%
“…For example, the plasma isoform is expressed by macrophages, which retain a portion of the activity, while the type II liver isoform is found in several soft tissues (7), particularly those rich in epithelial cells (8). Comprehensive analyses of the distribution of PAF-AHs have not been conducted, but this can be anticipated by the distribution of their mRNAs.…”
Section: Location Location Locationmentioning
confidence: 99%
“…Stafforini et al ( 25 ) showed that the secreted form of Lp-PLA 2 released F 2 -isoprostanes, the end products of lipid oxidation, from the sn-2 position of phosphatidylcholines with high affi nity. Kono et al ( 26 ) have reported that intracellular type II Lp-PLA 2 , which shares homology with the plasma enzyme Lp-PLA 2 , is involved in the metabolism of esterifi ed 8-iso-PGF 2 ␣ . Similar to previous fi ndings ( 3,27 ), this study also showed a positive correlation between changes in circulating Lp-PLA 2 activity and urinary 8-epi-PGF 2 ␣ concentrations.…”
Section: Downloaded Frommentioning
confidence: 99%